2021
DOI: 10.2147/jir.s307305
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Organ Transcriptome Dynamics in a Mouse Model of Cecal Ligation and Puncture-Induced Polymicrobial Sepsis

Abstract: Purpose During sepsis, an excessive inflammatory immune reaction contributes to multi-organ dysfunction syndrome (MODS), a critical condition associated with high morbidity and mortality; however, the molecular mechanisms driving MODS remain elusive. Methods We used RNA sequencing to characterize transcriptional changes in the early phase of sepsis, at 6, 12, 24 hour time points in lung, kidney, liver, and heart tissues, in a cecal ligation and puncture (CLP)-induced po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…We chose the heart, kidney, lung, and liver tissues for the RNA-Seq survey upon SCH772984 treatment as those organs are frequently affected in the course of sepsis [ 37 ]. Our recent RNA-seq transcriptomic survey of the same tissues 6 h, 12 h, and 24 h post-CLP procedure in mice indicated that the alteration of the immune system pathways is common across multiple organs, and the highest number of significant DEGs in those organs, when compared to sham-operated mice, is observed at 12 h [ 38 ]. Based on this observation and the fact that CLP mice start manifesting clinical signs of sepsis at around 12 h post-CLP [ 39 ], we selected the 6 h and 12 h time points to capture early molecular events of SCH772984 action.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the heart, kidney, lung, and liver tissues for the RNA-Seq survey upon SCH772984 treatment as those organs are frequently affected in the course of sepsis [ 37 ]. Our recent RNA-seq transcriptomic survey of the same tissues 6 h, 12 h, and 24 h post-CLP procedure in mice indicated that the alteration of the immune system pathways is common across multiple organs, and the highest number of significant DEGs in those organs, when compared to sham-operated mice, is observed at 12 h [ 38 ]. Based on this observation and the fact that CLP mice start manifesting clinical signs of sepsis at around 12 h post-CLP [ 39 ], we selected the 6 h and 12 h time points to capture early molecular events of SCH772984 action.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tested the above protocol using either proteinase K or TRIzol extraction from CryoCore samples taken from CryoTray-stored frozen livers of either LPS (endotoxin) or PBS (control) treated mice ( Fig.3A ). Isolated RNA was used in Matrix RT-qPCR using exon-spanning primers to the housekeeping Actb , and multiorgan sepsis-inducible Ngal ( Lcn2 ) genes (48,51). The CTs for Actb were much higher (lower mRNA levels) with the proteinase K method compared to TRIzol ( Fig.3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Matrix-RT-qPCR was used first to compare the PK buffer vs TRIzol protocol ( Fig.6A ) to assess the well-described organ-specific, sepsis-induced, and housekeeping mRNA expression patterns (1,48,51). Data are shown as both CTs and as a ratio to the Rpl32 housekeeping mRNA ( Fig.6B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations